Competition magnifies the impact of a pesticide in a warming world by reducing heat tolerance and increasing autotomy. (February 2018) - Op de Beeck, Lin; Verheyen, Julie; Stoks, Robby
Abstract: There is increasing concern that standard laboratory toxicity tests may be misleading when assessing the impact of toxicants, because they lack ecological realism. Both warming and biotic interactions have been identified to magnify the effects of toxicants. Moreover, while biotic interactions may change the impact of toxicants, toxicants may also change the impact of biotic interactions. However, studies looking at the impact of biotic interactions on the toxicity of pesticides and vice versa under warming are very scarce. Therefore, we tested how warming (+4 °C), intraspecific competition (density treatment) and exposure to the pesticide chlorpyrifos, both in isolation and in combination, affected mortality, cannibalism, growth and heat tolerance of low- and high-latitude populations of the damselfly Ischnura elegans . Moreover, we addressed whether toxicant exposure, potentially in interaction with competition and warming, increased the frequency of autotomy, a widespread antipredator mechanism. Competition increased the toxicity of chlorpyrifos and made it become lethal. Cannibalism was not affected by chlorpyrifos but increased at high density and under warming. Chlorpyrifos reduced heat tolerance but only when competition was high. This is the first demonstration that a biotic interaction can be a major determinant of 'toxicant-induced climate change sensitivity'. Competition enhanced the impact of chlorpyrifos under warming for high-latitude larvae, leading to an increase in autotomy which reduces fitness in the long term. This points to a novel pathway how transient pesticide pulses may cause delayed effects on populations in a warming world. Our results highlight that the interplay between biotic interactions and toxicants have a strong relevance for ecological risk assessment in a warming polluted world. Graphical abstract: Image 1 Highlights: Competition made the pesticide chlorpyrifos (CPF) become lethal. CPF exposure led to more autotomy but only at high density under warming. At high density CPF reduced the heat tolerance (CTmax). Competition can increase the toxicity and impact of a pesticide under warming. Abstract : Intraspecific competition increases the impact of an organophosphate pesticide under warming by increasing the amount of autotomy and by reducing heat tolerance.